2017
DOI: 10.3390/microarrays6020007
|View full text |Cite
|
Sign up to set email alerts
|

Avian and Mammalian Facilitative Glucose Transporters

Abstract: The GLUT members belong to a family of glucose transporter proteins that facilitate glucose transport across the cell membrane. The mammalian GLUT family consists of thirteen members (GLUTs 1–12 and H+-myo-inositol transporter (HMIT)). Humans have a recently duplicated GLUT member, GLUT14. Avians express the majority of GLUT members. The arrangement of multiple GLUTs across all somatic tissues signifies the important role of glucose across all organisms. Defects in glucose transport have been linked to metabol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 82 publications
3
32
0
2
Order By: Relevance
“…While the 537 presence of transcript does not necessarily mean that the final protein form is being fully 538 transcribed (Vogel and Marcotte, 2012), it is clear that hepatic GLUT1 is not translocated to the 539 plasma membrane. Our findings are similar to others that have failed to detect GLUT1 in the 540 avian liver (Byers et al, 2017;Carver et al, 2001), raising the possibility that the role of hepatic 541 GLUT1 protein may be much more reduced among birds than previously appreciated. 542…”
supporting
confidence: 89%
“…While the 537 presence of transcript does not necessarily mean that the final protein form is being fully 538 transcribed (Vogel and Marcotte, 2012), it is clear that hepatic GLUT1 is not translocated to the 539 plasma membrane. Our findings are similar to others that have failed to detect GLUT1 in the 540 avian liver (Byers et al, 2017;Carver et al, 2001), raising the possibility that the role of hepatic 541 GLUT1 protein may be much more reduced among birds than previously appreciated. 542…”
supporting
confidence: 89%
“…Studies have reported that during diabetes, the insulin-stimulated glucose uptake by GLUT-4 is largely hampered in muscle and adipose tissue leading to the development of insulin resistance. Studies have also reported that over expression of GLUT-4 in the adipose tissue of GLUT-4 knockout mice ameliorate insulin resistance, diabetes and enhance insulin sensitivity [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…As stated above, glucose and lactose also serve as significant energy source for myocardial cells. Glucose transporters (GLUT) are a family of proteins which mediate entry of glucose into cells [ 27 , 28 ]. Of these, GLUT4 is the most abundant glucose transporter in heart [ 29 ].…”
Section: Resultsmentioning
confidence: 99%